Variabilidade da densidade básica e de propriedades mecânica de madeiras da Amazônia. - Nascimento, Claudete Catenhede do (Universidade de São Paulo - USP, 1993)
The aim of this work was to study the variability and the distribution of the wood specific gravity values and five mechanical properties of 750 trees of 87 woody species from the Amazonas region. The wood from the tree species collected from Balbina and Tapajós or from Balbina and Curuá-Una regions showed significative differences from one region to another or were region independent on their specific gravity and mechanical properties. Through multivariate analyses were established five groups different among themselves but each one containing only species with wood having equivalent properties. This fact allowed to broaden the possibilities for substitution without the loss of mechanical quality of the traditional Amazonian timber species. Due to the interaction species x region, cases were observed where one determined species from one region was sit in one group and the same species callected in other region was sit in another group. The specific gravity was utilized as an indicator of the mechanical quality of the wood. Good relations among the different mechanical properties and the specific gravity were obtained fa the Amazonas region as a whole. By two adjustment methods, the functions of probabilistic and the acumulated function of the WEIBULL distribution adapted to the specific gravity were astarmed. These could be considered fully satisfactionies to explain the distribution of this important property in Amazonas forest. The functions of probabilistic and the functions of accumulated for each of the mechanical properties were obtained utiliziny only its respective relations with the specific gravity and the adjusted distributions for its own specific gravity. In this case, the dispersions amound the regressions were mistaken with the natural variability of the studied mechanical properties. This way, it was possible to transform the specific gravity in a unique and enough parameter necessary to the wood stucture projects.
Keywords: Madeiras do Amazônas